APLIKASI KAMUS BAHASA INDONESIA – BUGIS BERBASIS WEB DENGAN METODE SEQUENTIAL SEARCH - Anna Anna (Jurnal Informatika, 2016)
Abstract Everyone can interact with the others through a language. Indonesia is known as a country that has a lot of cultural diversity, one of the diversity is different languages in each region. Bugis language is one of the local language in Indonesia for Makassar typical society. At this time this language is reduced using. Even many Bugis’s people do not understand their own language. Those who live in the neighborhood instead of the original population of bugis tribe who were never taught the language of their origin region. One of the reason is lack of learning media for Bugis language so make peoples are lazy to learn it. Through the application of Indonesian - Bugis dictionary translation using web technology, every person can easily learning the language of Bugis. In addition to enabling users, a dictionary application created purpose to preserve one of Indonesia's cultural diversity which is the local language and that’s not to become extinct. This translation dictionary application is using Sequential Search algorithm (search in a row) for the word search processing. This search method is suitable use for an Indonesian - Bugis dictionary application because it can translate quickly search terms. Keywords: dictionary, Sequential Search, web applications, bugis language, algorithm.